Characterization and flocculation mechanism of a bioflocculant from hydrolyzate of rice stover. (February 2015) - Guo, Junyuan; Yu, Jing; Xin, Xin; Zou, Changwu; Cheng, Qingfeng; Yang, Huaijin; Nengzi, Lichao
Highlights: Hydrolyzate from acid treated rice stover were used to produce bioflocculant. Characteristics of the bioflocculant were examined. Flocculating mechanisms were detected by using kaolin suspension in present of Ca 2+ . The application of the bioflocculant in real wastewater treatment was investigated. Abstract: This study investigated the characterization and flocculation mechanism of a bioflocculant from hydrolyzate of rice stover. Production of the bioflocculant was positively associated with cell growth and a highest value of 2.4 g L −1 was obtained. During the kaolin suspension flocculation, charge neutralization and inter-particle bridging were proposed as the reasons for enhanced performance. Apart from this, the bioflocculant showed good performances in sludge dewatering and swine wastewater pretreatment. After conditioning by the bioflocculant, dry solids (DS) and specific resistance to filtration (SRF) of the sludge reached 18.4% and 4.8 × 10 12  m kg −1, respectively, which were much better than that by conventional chemical flocculants. In the swine wastewater pretreatment, the removal efficiencies of COD, ammonium, and turbidity reached 48.3%, 43.6% and 75.8% at pH 8.0 when the bioflocculant dose was adjusted to 20 mg L −1 .